LEXICAL REPETITION AS A COMPONENT OF STRATEGIC-TACTICAL INTERACTIONS OF CHARACTERS OF UKRAINIAN SMALL PROSЕ - Finiv , V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article it is established the role of the repeated nominations in the development and implementation of strategic-tactical narrative of character, it is also outlined here views of the linguists about the interpretation of concepts “lexical repetition”, “communicative strategy”, “communicative tactics”.